Causal Association between Saturated Fatty Acid Foods and Osteoarthritis and Identification of Potential Targets - Chen, Kaige; Li, Xingqiang; Zeng, Xueqin; Sun, Yindi (Journal of Contemporary Medical Practice, 2024)
Background: Numerous studies suggest a link between the consumption of foods rich in saturated fatty acids and the development of osteoarthritis. However, the causal relationships are still unclear. Moreover, the complex pathogenesis poses challenges in developing targeted drugs and identifying biomarkers. Objective: To investigate the potential causal association between the consumption of foods in saturated fatty acids and osteoarthritis, as well as to identify potential therapeutic targets and biomarkers using colocalization analysis. Methods: A two-sample Mendelian randomization (MR) analysis based on publicly available genome-wide association studies was employed to infer the causal relationship. The effect estimates were calculated using the random-effects inverse-variance-weighted method. Bayesian colocalization analysis was conducted to identify potential therapeutic targets and metabolic products. Results: Cheese intake per standard deviation increase causally reduced the risks of knee osteoarthritis (OR = 0.605; 95% CI, 0.479-0.764; p < 0.001), osteoarthritis of the hip or knee (OR = 0.676; 95% CI, 0.553-0.826; p < 0.001), and osteoarthritis self-reported (OR = 0.720; 95% CI, 0.521-0.995; p = 0.047). Cheesy biscuits intake per standard deviation increase causally reduced the risks of knee osteoarthritis (OR = 0.485; 95% CI, 0.239-0.987; p = 0.046), osteoarthritis of the hip or knee (OR = 0.535; 95% CI, 0.315-0.909; p = 0.021). Pork intake per standard deviation increase causally reduced the level of basophil (OR = 0.738; 95% CI,0.579-0.941; p = 0.014); each standard deviation increase in mutton intake reduced the level of CRP (OR = 0.763; 95% CI. 0.594-0.979; p = 0.034), each additional standard deviation of whole milk intake reduced the level of CRP (OR = 0.079; 95% CI, 0.008-0.737; p = 0.026), and each additional standard deviation of fried potato intake reduced the level of the neutrophil count (OR = 0.944; 95% CI, 0.892-0.999; p = 0.048). Three single nucleotide polymorphisms (SNPs), namely rs143384, rs66989638, and rs8053839, associated with knee or hip osteoarthritis, as well as one SNP (rs112635299) associated with osteoarthritis metabolism, were identified through colocalization analysis. Conclusions: This two sample MR analysis found a causal negative association between foods containing saturated fatty acids and both osteoarthritis and biomarkers. Colocalization analysis identified three potential drug targets and one metabolite that could serve as a diagnostic marker.